The Tax-Spend Debate: Time Series Evidence from Sarawak Municipals, 1975-2003 - Muzafar Shah, Habibullah; Dayang Affizzah, Awang Marikan (Hyderabad ICFAI University Press, 2008)
This paper is concerned with the issue of the intertemporal relationship between revenues and expenditures and the way in which a State Government manages public deficits. In this study, different hypotheses are considered to examine such a problem. The so called tax-spend hypothesis postulates that government raises tax revenues ahead of engaging in new expenditures. The spend-tax hypothesis, on the other hand, predicts that government first spends and then increases tax revenues to finance their expenditures. There is also the fiscal synchronization hypothesis which suggests that government takes simultaneous decisions about revenues and expenditures. Lastly, there is independence regarding the decisions to spend and raise revenues. Using the annual data on revenues and expenditures for the 22 municipals in Sarawak for the period 1975-2003, the cointegration and vector error correction model analyses suggest that the results are at best mixed.